PENERAPAN SIKADESTROPIK UNTUK PENCEGAHAN PENYAKIT KATASTROPIK BAGI KADER POSYANDU LANSIA DESA WIRU KECAMATAN BRINGIN KABUPATEN SEMARANG - Sari, Devi Pramita; Nabilatul Fanny; Fifi Anisa Nur Hidayati (P3M Universitas Aisyiyah Surakarta, 2024)
Catastrophic disease is a disease that requires long and high cost medical treatment. Diseases included in the catastrophic group include hypertension, diabetes mellitus, and stroke. In the preliminary study it was found that those with catastrophic diseases were also a group that received serious attention from elderly posyandu cadres in Wiru Village because 366 elderly people in Wiru Village suffered from catastrophic diseases, 305 elderly people had a low economic level out of a total of 610 elderly people, lack of adequate treatment optimal results from elderly and village posyandu cadres, and it is known that the lack of training obtained by elderly posyandu cadres for knowledge related to catastrophic diseases. The purpose of this PkM activity is to increase the knowledge of elderly posyandu cadres through digital-based education by implementing the Catastrophic Hospital Calculator Information System (SIKADESTROPIK). This is what underlies the holding of community service with the title